A common variant association study in ethnic Saudi Arabs reveals novel susceptibility loci for hypertriglyceridemia. Issue 3 (30th January 2017) - Ram, R.; Wakil, S.M.; Muiya, N.P.; Andres, E.; Mazhar, N.; Hagos, S.; Alshahid, M.; Meyer, B.F.; Morahan, G.; Dzimiri, N.
Abstract : Hypertriglyceridemia (hTG) is a lipid disorder, resulting from an elevation in triglyceride levels, with a strong genetic component. It constitutes a significant risk factor for coronary artery disease (CAD), a leading cause of death worldwide. In this study, we performed a common variant association study for hTG in ethnic Saudi Arabs. We genotyped 5501 individuals in a two‐phase experiment using Affymetrix Axiom ® Genome‐Wide CEU 1 Array (Affymetrix, Santa Cruz, CA) that contains a total of 587, 352 single nucleotide polymorphisms (SNPs). The lead variant was the rs1558861 [1.99 (1.73–2.30); p = 7.37 × 10 −22 ], residing on chromosome (chr) 11 at the apolipoprotein A‐I/A‐5 ( APOA1 / APOA5 ) locus. The rs780094 [1.34 (1.21–1.49); p = 8.57 × 10 −8 ] on chr 2 at the glucokinase regulatory protein ( GCKR ) locus was similarly significantly associated, while the rs10911205 [1.29 (1.16–1.44); p = 3.52 × 10 −6 ] on chr1 at the laminin subunit gamma‐1 ( LAMC1 ) locus showed suggestive association with disease. Furthermore, the rs17145738 [0.68 (0.60–0.77); p = 6.69 × 10 −9 ] on chr7 at the carbohydrate‐responsive element‐binding protein‐encoding ( MLXIPL ) gene locus displayed significant protective characteristics, while another variant rs6982502 [0.76 (0.68–0.84); p = 5.31 × 10 −7 ] on chr8 showed similar but weaker properties. These findings were replicated in 317 cases vs 1415 controls from the same ethnic Arab population. Our study identified several variants across the human genome that are associated with hTG in ethnic Arabs. Abstract :